2021
DOI: 10.3389/fcimb.2021.685657
|View full text |Cite
|
Sign up to set email alerts
|

A New Species-Specific Typing Method for Salivarius Group Streptococci Based on the Dephospho-Coenzyme A Kinase (coaE) Gene Sequencing

Abstract: Viridans streptococci are a group of α-hemolytic streptococcal species. They are mainly commensals, most abundant in the mouth supporting oral health. But they also include important human pathogens such as Streptococcus pneumoniae. Identification and molecular typing of viridans group streptococci are challenging, especially for members of the salivarius group. In this study, we developed a single-locus molecular typing method that is able to differentiate among the highly phylogenetically related members of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Previous studies have reported a close similarity between S. vestibularis and S. salivarius based on phylogenetic analysis of the 16S rRNA gene sequence ( Pombert et al, 2009 ). Here, we employed the coaE ( Abdelbary et al, 2021 ) gene-based phylogenetic tree to demonstrate a closer relationship between S. vestibularis and S. thermophilus.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have reported a close similarity between S. vestibularis and S. salivarius based on phylogenetic analysis of the 16S rRNA gene sequence ( Pombert et al, 2009 ). Here, we employed the coaE ( Abdelbary et al, 2021 ) gene-based phylogenetic tree to demonstrate a closer relationship between S. vestibularis and S. thermophilus.…”
Section: Resultsmentioning
confidence: 99%
“…Given their shared physiological traits and habitat, it is reasonable to assume that S. salivarius and S. vestibularis are more closely related to each other than to S. thermophilus. Recent phylogenetic analyses presented in a study strongly support the sister relationship between S. vestibularis and S. thermophilus, with S. salivarius diverging earlier at the base of the salivarius clade (Pombert et al, 2009;Abdelbary et al, 2021). Identifying and typing viridans group streptococci has proven challenging in multiple reports.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…20 The S. salivarius group of the genus Streptococcus is a cluster significantly supported by the data of sequence analysis using the 16S rRNA, rnpB, and coaE genes from the core streptococcal genome. 14 16S rRNA is widely used to determine the S. salivarius group. However, it is difficult to identify the group species using the 16S rRNA region.…”
Section: Discussionmentioning
confidence: 99%
“…PCR amplification in the coaE gene was performed using the following primers: forward primer coaE-SG-fwd 5 0 -TTAACAGGWGGYATTGCTTCAG-3 0 and reverse primer coaE-SG-rev 5 0 -CTTMACCTTCTYCTTCAAATCATC-3 0 were used. The PCR program involved an initial denaturation step at 94°C for 1 min, followed by 30 cycles (each cycle consisting of 94°C for 30 s, 51°C for 30 s, and 72°C for 1 min) of reactions terminated by a final extension step at 72°C for 4 min 14 Sequence analysis of the coaE gene was similar to that of the 16S rRNA gene described above. We also performed phylogenetic analysis to study the evolutionary relationships between organisms based on their genetic sequences.…”
Section: Incubation and Culture Of S Salivarius Coloniesmentioning
confidence: 99%